2011
DOI: 10.1126/science.1201351
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Preparation of a Tunable Few-Fermion System

Abstract: authors contributed equally to this work.Systems consisting of few interacting fermions are the building blocks of matter, with atoms and nuclei being the most prominent examples. We have created a few-body quantum system with complete control over its quantum state using ultracold fermionic atoms in an optical dipole trap. Ground-state systems consisting of 1 to 10 particles were prepared with fidelities of ∼ 90%. We can tune the interparticle interactions to arbitrary values using a Feshbach resonance and ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
723
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 507 publications
(732 citation statements)
references
References 27 publications
8
723
0
1
Order By: Relevance
“…We have shown that our proposal allows to stabilize a number of interesting quantum Hall states, such as the Pfaffian, and the n ¼ 1/3 Laughlin state. In our numerical calculation we have considered a small number of atoms, as it has become experimentally feasible recently [38][39][40] , but we note that the scheme should also be applicable to large systems. A good candidate for realizing the proposal are ytterbium atoms due to the long-lived state of the clock transition.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that our proposal allows to stabilize a number of interesting quantum Hall states, such as the Pfaffian, and the n ¼ 1/3 Laughlin state. In our numerical calculation we have considered a small number of atoms, as it has become experimentally feasible recently [38][39][40] , but we note that the scheme should also be applicable to large systems. A good candidate for realizing the proposal are ytterbium atoms due to the long-lived state of the clock transition.…”
Section: Discussionmentioning
confidence: 99%
“…Then one must explicitly use the discrete spectrum and the quantum numbers of the harmonic trap. In this respect, tight traps with very few particles is the case most closely related to nuclei (Serwane et al 2011, Zürn et al 2012). Alternatively, a very deep periodic optical lattice potential can have single sites that are approximately harmonic and contain only a few particles (Bloch et al 2008), again closer to the situation in small nuclei.…”
Section: Two-component Atomic Fermi Gasesmentioning
confidence: 99%
“…Usually the number of atoms in a cold atomic gas experiment has been of order 10 3 − 10 6 and a theoretical approach based on few-body methods is obviously doomed. However, recently microtraps have been built that are capable of trapping very few atoms (1 − 10) at very low temperatures (Serwane et al 2011, Zürn et al 2012. Furthermore, it is now possible to address single lattice sites in an optical lattice and produce and probe only a few atoms on such a site (Bakr et al 2010, Sherson et al 2010, Weitenberg et al 2011).…”
Section: Fermionic Few-body Systemsmentioning
confidence: 99%
See 2 more Smart Citations